2015
DOI: 10.1093/mutage/gev034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exposure to wood dust on genotoxicity and cytotoxicity in exfoliated buccal and nasal cells

Abstract: Wood dust was classified by the IARC as a human carcinogen which causes sinonasal tumours. However, the exposure in different industries varies strongly and the risks of workers depend on the specific situation which can be assessed by the use of biomonitoring methods. The aim of this study was to investigate the workers who are exposed to low dust levels (below the permitted concentrations) with cytogenetic and biochemical methods. Micronuclei (MNi) which are indicative for genomic damage, nuclear buds which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 47 publications
4
10
0
Order By: Relevance
“…It has been established that chromatin shrinkage followed by disruption of the nuclear membrane may result in cytotoxicity (21). Some authors have postulated that chronic exposure to genotoxins induced an increase in cell death in buccal epithelium of humans (19,20). Our results are fully in agreement with these findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been established that chromatin shrinkage followed by disruption of the nuclear membrane may result in cytotoxicity (21). Some authors have postulated that chronic exposure to genotoxins induced an increase in cell death in buccal epithelium of humans (19,20). Our results are fully in agreement with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…By comparison, some studies have demonstrated increased frequencies of micronuclei in such cells from agricultural workers exposed to pesticide mixtures in Guerrero state, Mexico (18). On the other hand, no induction of micronucleated cells was observed in buccal epithelia in people exposed to wood dust (19). Similarly, residents in Vietman did not show remarkable differences for micronucleus frequency in buccal mucosa cells after 40 years of dioxin exposure (20).…”
Section: Discussionmentioning
confidence: 95%
“…Micronuclei confirm mutagenesis in cells and living tissues, which corresponds to the initiation phase of carcinogenesis (18). For this reason, the detection of an elevated frequency of micronuclei in eukaryotic cells indicates genomic instability as far as increased cancer risk (19). Our results demonstrated an increased micronucleus frequency in buccal cells of street sweepers when compared to those from matched controls.…”
Section: Discussionsupporting
confidence: 62%
“…An enhanced risk for chromosomal instability was found in wood workers . Discrepant results have been reported (Wultsch et al, 2015). In that study, no induction of micronuclei was observed in wood workers exposed to 0.39-0.66 mg/m 3 wood dust levels.…”
Section: Introductionmentioning
confidence: 67%